Late-Life Depression in Home Healthcare - Pickett, Yolonda (2012)
Major depression is disproportionately common among elderly adults receiving home healthcare and is characterized by greater medical illness, functional impairment, and pain. Depression is persistent in this population and is associated with numerous poor outcomes such as increased risk of hospitalization, injury-producing falls, and higher health care costs. Despite the need for mental health care in these patients, significant barriers unique to the home healthcare setting contribute to under-detection and under-treatment of depression. Intervention models target the home healthcare nurse as liaison between patients and physicians, and instruct in the identification and management of depression for their patients. Successful implementation requires interventions that ‘fit’ how home healthcare is organized and practiced, and long distance implementation strategies are required to increase the reach of these interventions.